Simplify the following expressions:

1. cos(180° + x) + cos(180° - x)

2. cos(126°)cos(36°) + sin(126°)sin(36°)

### 1 Answer | Add Yours

The expression

cos(180° + x) + cos(180° - x)

=> -cos x - cos x

=> -2*cos x

cos(126°)cos(36°) + sin(126°)sin(36°)

=> -sin 36°*cos(36°) + cos 36°*sin(36°)

=> 0

**cos(180° + x) + cos(180° - x) = -2*cos x and cos(126°)cos(36°) + sin(126°)sin(36°) = 0**

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes